Abdominal compartment syndrome due to extremely elongated sigmoid colon and rectum plus fecal impaction caused by disuse syndrome and diabetic neuropathy: a case report and review of the literature - Usuda, Daisuke (J Med Case Rep, 2020)
BACKGROUND: Abdominal compartment syndrome (ACS) is defined as a sustained raised level of intra-abdominal pressure more than 20 mmHg with or without abdominal perfusion pressure less than 60 mmHg and the development of new end-organ failure. Abdominal surgery, major trauma, volvulus, ileus, distended abdomen, fecal impaction, acute pancreatitis, liver dysfunction, sepsis, shock, obesity, and age have all been reported as risk factors. Herein, we report the severest known case of ACS due to extremely elongated sigmoid colon and rectum plus fecal impaction caused by disuse syndrome and diabetic neuropathy, together with a brief review of the literature. CASE PRESENTATION: A 48-year-old Asian man suffering from shock was transported by ambulance to our hospital. His medical history included hypoglycemic encephalopathy sequelae, disuse syndrome, type 2 diabetic neuropathy, and constipation. He recovered consciousness in the ambulance, and his physical examination as well as laboratory findings were normal. X-ray and dynamic computed tomography revealed a thickened gut wall, and an extremely dilated sigmoid colon and rectum filled with a massive amount of stool as well as gas, compressing other intra-abdominal organs. We diagnosed the patient with transient vasovagal syncope, together with ACS, due to extremely elongated sigmoid colon and rectum plus fecal impaction, caused by anorectal disturbance derived from disuse syndrome and diabetic neuropathy. We first repeated stool extraction for bowel decompression and he subsequently became symptom-free, after which we performed a colostomy on the 28th hospital day. The postoperative course was uncomplicated, and he was discharged on the 44th hospital day. CONCLUSIONS: Clinicians need to keep ACS in mind as a differential diagnosis and perform careful and detailed examination when encountering patients presenting with symptoms or risk factors of ACS. In addition, they need to precisely diagnose ACS and perform optimal treatment without delay.